Research on innovation input of manage strategy based on data analysis. Issue 1 (June 2021) - Liu, Liangcan; Gu, Wenjie
Abstract: Self-occupaied operation is a common mode of operation in Chinese management, and self-occupaied innovation can help maintaining their core competitiveness and achieving a favorable position. For the purpose of exploring the influence on innovation input, this paper uses the data of A-share listed objects in China from 2016 to 2019, and uses the method of data analysis to perceive the effect on innovation input. The results show that self-occupaied objects are less willing to innovate. Further analysis shows that income constraints strengthen the relationship between objects and relative connections innovation input. Under income constraints, self-occupaied object is better tend to reduce innovation input. This paper improves the research on the innovation and has certain reference significance to the innovation management in China.